HUBUNGAN PENGETAHUAN DAN SIKAP DENGAN KEJADIAN HIPERTENSI DI WILAYAH KERJA PUSKESMAS TATELI KABUPATEN MINAHASA - Limbong, Valdano A.; Rumayar, Adisti; Kandou, Grace D. (Sam Ratulangi University, 2018)
Kasus hipertensi di Sulawesi Utara meningkat dari tahun ke tahun. Kabupaten Minahasa termasuk dari wilayah di Sulawesi Utara dengan prevalensi hipertensi. > 40%. Puskemas Tateli yang merupakan salah satu Puskesmas di Kabupaten Minahasa, dimana pada tahun 2014 kejadian hipertensi menepati urutan kedua dengan angka kejadian 669 kasus. Tujuan penelitian ini untuk mengetahui hubungan pengetahuan dan sikap dengan kejadian hipertensi pada masyarakat di wilayah kerja Puskesmas Tateli Kabupaten Minahasa. Penelitian ini merupakan penelitian survei analitik dengan pendekatan cross sectional. Penelitian ini dilaksanakan di wilayah kerja Puskesmas Tateli pada bulan Januari tahun 2016. Populasi dalam penelitian ini adalah penduduk di wilayah kerja Puskesmas Tateli Kecamatan Pineleng jumlah 669 orang. Pengambilan sampel menggunakan rumus Slovin sebanyak 90 Pasien. Analisis data menggunakan analisis univariat dan analisis bivariat. Analisis statistik menggunakan Chi Square pada tingkat kepercayaan 95% (á½°=0,05). Analisis hubungan antara pengetahuan masyarakat dengan kejadian hipertensi diperoleh p value = 0,000, dan analisis hubungan antara sikap dengan kejadian hipertensi diperoleh p value = 0,003.Kata Kunci : Pengetahuan, Sikap, Kejadian Hipertensi, Hipertensi TateliABSTRACTHypertension cases in North Sulawesi increase from year to year. Minahasa Regency is included in the region in North Sulawesi with the prevalence of hypertension. > 40%. Tateli Puskemas which is one of the Puskesmas in the Minahasa District, where in 2014 the incidence of hypertension kept the second order with an incidence of 669 cases. The purpose of this study was to determine the relationship between knowledge and attitudes with the incidence of hypertension in the community in the working area of the Tateli Health Center in Minahasa Regency. This research is an survey analytic study with a cross sectional approach. This research was dilaksanakan out in the Tateli Community Health Center working area in January 2016. The population in this study were patients who settled in Tateli village, Pineleng sub-district with the number 669 people. Sampling was using the Slovin formula as many as 90 patients. Data analysis used univariate analysis and bivariate analysis. Statistical analysis using Chi Square at a 95% confidence level (á½° = 0.05). Analysis of the relationship between community knowledge with the incidence of hypertension obtained p value = 0,000, and an analysis of the relationship between attitudes and the incidence of hypertension was obtained p value = 0.003. there is relationship between knowledge and attitudes of people with the incidence of hypertension in the working area of the Tateli Health Center districts Mandolang Minahasa Regency. for the government further improve counseling programs on hypertension, for side the Puskesmas to be able work together with other health institution how to socialize health in Tateli village. This research would be a motivation for other college student and subsequent researchers to conduct broader research.Keywords: Knowledge, Attitude, Hypertension, Hypertension Tateli